An improved approach to the prediction of line current spectrum in induction machines - Guldemir, H; Bradley, KJ (Springer, 2003)
This paper concentrates on the estimation of the magnitude and frequency of the spectral components of line current that may be used for sensorless speed detection. The prediction method uses a mixture of permeance-magnetomotive force, finite element and reluctance mesh techniques to establish the airgap magnetic field. This traditional type of approach is chosen to maintain a visible link between cause and effect, so enhancing understanding of complex interactions. The approach is enhanced by the use of slot permeance effects calculated by finite element techniques, where saturation due to the current carrying conductors in the slots is incorporated. Further enhancements include examining slot permeance effects over one or more poles so that the influence of the spatial distribution of slot currents and slot top saturation can be incorporated. The large number of independent speed harmonic terms found experimentally in the line current spectrum is explained by rotor pole aliasing. Special equivalent circuits are introduced to enable these current harmonics to be predicted. A thorough experimental validation of the model is then conducted using a 30-kW experimental machine with adjustable eccentricity, rotors of different slotting form, slot number and skew to determine their effect on the speed-dependent harmonic components. Very good agreement was observed.
Keywords: induction motor; current spectrum; slot harmonics; permeance; airgap field